Camelids Nanobodies: Novel Prophylactic and Therapeutic Medication Against Epstein-Barr Virus Infection by Targeting Glycoprotein B - Bastawecy, Iman M.; Afify, Ahmed F.; Abdelmonem, Mohamed; Gamal, Fatima-Alzahraa; Alhadad, Maha A. (European Journal of Applied Sciences, 2025)
The Epstein-Barr virus (EBV) represents a widespread pathogen that infects nearly 98% of adults worldwide, creating persistent latent infections throughout the host’s lifetime while contributing to various pathological conditions, encompassing malignancies and autoimmune diseases. EBV’s presence within peripheral blood lymphocytes enables transmission through blood transfusion procedures and organ transplantation, creating substantial hazards, especially for immunocompromised patients including transplant recipients who face elevated vulnerability to EBV-associated lymphoproliferative conditions. Presently, neither efficacious vaccination programs nor specific antiviral treatments for EBV are available, highlighting the critical requirement for innovative preventive and treatment approaches. Glycoprotein B (gB) serves as a vital viral fusion protein, performing essential functions in EBV cellular entry, intercellular transmission, viral particle development, and nuclear exodus. Significantly, EBV particles containing elevated gB levels demonstrate superior infectious capacity, with gB establishing direct binding interactions with neuropilin-1 (NRP1) throughout epithelial cell and B lymphocyte invasion processes. Earlier studies demonstrate that EBV-gB successfully stimulates neutralizing antibody responses, establishing its potential as an optimal therapeutic target. This analysis suggests creating camelid-derived single-domain antibody components (VHHs), termed nanobodies (Nbs), directed against EBV-gB. These Nbs, measuring approximately 15 kDa, demonstrate substantially reduced size compared to traditional antibodies, being devoid of light chains and CH1 domains. Their distinctive characteristics encompass simplified production processes, exceptional stability, superior solubility, improved tissue and tumor infiltration capabilities, plus blood-brain barrier crossing potential. Importantly, Nbs demonstrate minimal immunogenic properties, reducing unwanted reactions. Large-volume Nb manufacturing could deliver easily administered prophylaxis for high-risk populations or therapeutic intervention for active infections. Camelid immunization using EBV-gB would simultaneously enable production of powerful neutralizing Nbs while permitting assessment of gB’s vaccine potential. The extraordinary properties of Nbs constitute remarkable progress in therapeutic innovation, and we recommend focused initiatives to transform this promise into effective EBV treatments.